Preoperative staging of cholangiocarcinoma and biliary carcinoma using 18F-fluorodeoxyglucose positron emission tomography: a meta-analysis. (14th September 2017) - Hu, Jing-Hong; Tang, Jui-hsiang; Lin, Cheng-Hui; Chu, Yin-Yi; Liu, Nai-Jen
Abstract : This meta-analysis was performed to determine the diagnostic accuracy of 18F-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) in assessing primary cholangiocarcinoma (CCA) and CCA with lymph node and distant metastasis. A literature search for studies reporting the use of 18F-FDG-PET for preoperative work-up/staging in patients with CCA was performed. Diagnostic OR (DOR) was used as an index of diagnostic performance of FDG-PET/CT in predicting primary CCA, lymph node metastases, and distant metastases. The pooled DOR was 9.34 (95% CI 4.27 to 20.42) and the area under the summary receiver operating characteristic (SROC) curve was 0.8643 (SE=0.0362), indicating overall good discriminatory test performance in predicting primary CCA. Subgroup analyses based on the primary tumor site showed better diagnostic performance for intrahepatic CCA (DOR=54.44, 95% CI 13.44 to 220.49), both intrahepatic and extrahepatic CCA (DOR=32.96, 95% CI 1.41 to 768.80) and gallbladder cancer (DOR=12.93, 95% CI 1.97 to 84.80), than for extrahepatic CCA (DOR=2.55, 95% CI 0.71 to 9.20) and hilar CCA (DOR=2.75, 95% CI 0.17 to 43.72). The pooled DOR for the prediction of lymph nodes metastases in 10 studies was 11.34 (95% CI 4.79 to 26.80), with moderate heterogeneity (Cochran Q=15.14, p=0.0872, I 2 =40.5%). The area under the SROC curve was 0.8584 (SE=0.0729). In conclusion, 18F-FDG-PET and PET/CT were found to be accurate in the evaluation of primary tumors, lymph node metastasis, and distant metastasis in patients with CCA.